Beckman Model G pH meter, top shot of panel - Dietrich, T. A.
Arnold Beckman invented his first pH meter in 1934 at the request of a chemist from the California citrus industry, who needed an accurate way to measure the acidity of his product. The resulting “acidimeter” with its glass electrode was renamed the Model G pH meter in 1937 and produced on a larger scale by Beckman’s company, National Technical Laboratories. This instrument kicked off the rapid development not only of NTL and Beckman Instruments, but also of the electronic scientific instrument industry.
Keywords: Hydrogen-ion concentration--Measurement--Instruments; Scientific apparatus and instruments; Hydrogen-ion concentration; Beckman Instruments, Inc.